Germ Cell Protocols Volume 1: Sperm and Oocyte Analysis - Schatten, Heide (Methods in Molecular Biology™, 2004)
Germ cell research has produced enormous advances in recent years and more recently has entered into an explosive phase of new discoveries with the introduction of transgenic technologies and nuclear cloning. In Germ Cell Protocols, expert laboratory investigators describe in step-by-step detail a series of powerful techniques for the molecular and genetic analysis of germ cells in a variety of different reproductive systems. Chosen for their proven success in advancing our understanding of germ cells, these methods cover sperm and egg activation, motility, fertilization, nuclear development, nuclear cloning, the molecular characterization of specific events, and the imaging of cell structures. Volume 1: Sperm and Oocyte Analysis focuses on sperm cells, oocyte analysis, oocyte maturation, fertilization, and preparation techniques. Highlights include in vitro maturation and fertilization of human, porcine, and canine oocytes; the cryopreservation of sperm cells; establishment of an in vitro spermatogenesis system; visualization of sperm accessory structures; and motility assays of spermatozoa. Each readily reproducible protocol is described in step-by-step detail and contains an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. An accompanying second volume, Molecular Embryo Analysis, Live Imaging, Transgenesis, and Cloning, contains methods for molecular egg analysis, live egg imaging, nuclear cloning, oocyte preservation, and nuclear transfer. Comprehensive and cutting-edge, Germ Cell Protocols offers both novice and established researchers a gold-standard collection of hard-to-find methods for high impact research, diverse procedures that are easy-to-follow, well-illustrated, and allow a cross-species transfer of knowledge from lower vertebrates to higher mammalian systems